STROKE SEVERITY ANALYSIS THROUGH CT-SCAN IMAGE TEXTURE ANALYSIS OF THE BRAIN WITH GRAY LEVEL RUN LENGTH MATRIX METHOD - Mulyono, Agus; Muthmainnah, Muthmainnah; Anripa, Nuralfin (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
The condition of a stroke is when the blood supply to the brain is disrupted due to a blockage (ischemicstroke) or rupture of a blood vessel (hemorrhagic stroke). This condition causes certain areas of thebrain to be deprived of the supply of oxygen and nutrients resulting in the death of brain cells. Thisstudy aims to determine the process of ischemic stroke assistance and hemorrhagic analysis through CTScan image texture GLRLM brain method with the classification method using discriminant analysisand determine the level of accuracy. In this study there are 3 stages, namely preprocessing, learningstages and testing stages. The results of the assessment of stroke in the ischemic and hemorrhagiccategories through texture analysis of CT scan images using the GLRLM brain method with aclassification accuracy of 100%.